Adverse Drug Reactions in Children: The Double‐Edged Sword of Therapeutics. Issue 6 (29th April 2017) - Elzagallaai, AA; Greff, MJE; Rieder, MJ
Abstract : Adverse drug reactions (ADRs) represent a major health problem worldwide, with high morbidity and mortality rates. ADRs are classified into Type A (augmented) and Type B (bizarre) ADRs, with the former group being more common and the latter less common but often severe and clinically more problematic due to their unpredictable nature and occurrence at any dose. Pediatric populations are especially vulnerable to ADRs due to the lack of data for this age group from the drug development process and because of the wide use of off‐label and unlicensed use of drugs. Children are more prone to specific types of ADRs because of the level of maturity of body systems involved in absorption, metabolism, transportation, and elimination of drugs. This state‐of‐the‐art review provides an overview of definitions, classifications, epidemiology, and pathophysiology of ADRs and discusses the available evidence for related risk factors and causes of ADRs in the pediatric population.